Mohammad Ilyas dan Gagasannya tentang Kalender Islam Internasional - Susiknan Azhari (Al-Jami'ah Research Centre, 2001)
This paper describes Muhammad llyas’ thought on international Islamic Calendar and its position in Contemporary Islamic studies. Ilyas is one of Muslim thinkers who tries very hard in uniting lslamic calendar around the world. Actually, his methodological efforts is a further development of a tradition which had been developed by previous Muslim thinkers such as ibn taymiyah, Ahmad Muhammad Syakir, abu Zahrah and T.M. Hasby as-Shiddiqy. However, these thinkers had only used normative-deductive domain. While Ilyas has not only dealt with normative-deductive domain but also empirical-inductive data using modern Science. For supporting his views, Ilyas conducted many research for about 20 years (1973-1993). For llyas, scientific study on International islamic calendar cannot be set aside because it is aproduc to history in which the role of reason or ijtihad is more dominant in producing it by basing on data taken from nafural phenomenon.Therefor, Ilyas argued that dialog on lntemational lslamic Calendar,especially on problem of lntemational Lunar Dateline (ILDL) will run well and harmonious if each representative of nation has a good education and holistic-comprehensive understanding. Ilyas believes that his effort will be realized especially after he knows Muslim’s ability and quality in sciences have been improved and wide spread. Apart from how later responses on his lnternational lslamic calendar will rise, what has been developed by Ilyas through his project of international Islamic Calendar program (IICP) and other works is renewal of the existing calendar. Therefore, his existence in contemporary Islamic studies is very significant in order that we will not be trapped into existing mapping of contemporary Islamic Thought, namely Theology, law, Philosophy, and Sufism. Thus, we need to include science in contemporary Islamic Studies.